The Iraqi Press Tendencies Toward The youth problems An analytical study in , Al – Mada Newspaper Iraqi: for the duration from 1-1-2018 to 31-3-2018 - Ali, Yusra Hamza (Al-Adab Journal, 2020)
This research aims to find out the Iraqi Press’ attitude in regards to the problems of the youth. Its goals focus on answering questions that came into light during the research process and to identify the most important problems facing young people which received the attention of the Iraqi press. It also studies the important journalistic arts that dealt with the problems of the youth. This research is descriptive in terms of gender, as the researcher used the survey method, and the method of content analysis represented by (5) major groups and (25) subcategories of press content to achieve the research’s objectives. The major results the research reached are:Studying the trends and methods of presenting the content of youth problems in the Iraqi press, as it appeared (in a negative direction) in Al-Mada newspaper, which explains the process of its presentation of topics and criticism of those in a responsible position through its various arts, as well as the lack of its solutions, if any, they are patchwork solutions and not radical solutions.